Larval development of the subantarctic king crabs Lithodes santolla and Paralomis granulosa reared in the laboratory - Calcagno, Javier Ángel; Anger, K.; Lovrich, Gustavo Alejandro; Thatje, S.; Kaffenberger, A. (Helgoland Marine Research)
The larval development and survival in the two subantarctic lithodid crabs Lithodes santolla (Jaquinot) and Paralomis granulosa (Molina) from the Argentine Beagle Channel were studied in laboratory cultures. In L. santolla, larval development lasted about 70 days, passing through three zoeal stages and the megalopa stage, with a duration of approximately 4, 7, 11 and 48 days, respectively. The larval development in P. granulosa is more abbreviated, comprising only two zoeal stages and the megalopa stage, with 6, 11 and 43 days' duration, respectively. In both species, we tested for effects of presence versus absence of food (Artemia nauplii) on larval development duration and survival rate. In P. granulosa, we also studied effects of different rearing conditions, such as individual versus mass cultures, as well as aerated versus unaerated cultures. No differences in larval development duration and survival were observed between animals subjected to those different rearing conditions. The lack of response to the presence or absence of potential food confirms, in both species, a complete lecithotrophic mode of larval development. Since lithodid crabs are of high economic importance in the artisanal fishery in the southernmost parts of South America, the knowledge of optimal rearing conditions for lithodid larvae is essential for future attempts at repopulating the collapsing natural stocks off Tierra del Fuego. Fil: Calcagno, Javier Ángel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Anger, K. Alfred Wegener Institute for Polar and Marine Research; Alemania Fil: Lovrich, Gustavo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Thatje, S. Alfred Wegener Institute for Polar and Marine Research; Alemania Fil: Kaffenberger, A. Alfred Wegener Institute for Polar and Marine Research; Alemania